The Vega Factor Oil Volatility and the Next Global Crisis - Moors, Kent F. 1948-; 1940- 1950-; 1950- 1963- (Hoboken, N.J. John Wiley & Sons, Inc., 2011)
How oil volatility is affecting the global political scene, and where the oil market is heading The world is rapidly moving towards an oil environment defined by volatility. The Vega Factor: Oil Volatility and the Next Global Crisis takes an in-depth look at the most important topics in the industry, including strategic risk, why traditional pricing mechanisms will no longer govern the market, and how the current government approaches have only worsened an already bad situation. Details the industry's players, including companies, traders, and governments Describes the priorities that will need to be revised, and the policies needed to achieve stability Explains how today's oil market is fundamentally different from the pre-crisis market Oil prices affect everyone. The Vega Factor explains the new international oil environment of increasing consolidation and decreasing competition, and reveals how consumers and investors can navigate price volatility and new government policies
Includes bibliographical references (pages 305-420) and index.
Keywords: Petroleum products -- Prices; Petroleum industry and trade; Petroleum reserves -- Political aspects; Petroleum products; Petroleum industry